Orchid Obscurity: Understanding Domestic Trade in Wild-Harvested Orchids in Viet Nam - Bullough, Leigh-Anne; Nguyễn, Nga; Drury, Rebecca; Hinsley, Amy (Frontiers in Ecology and Evolution, 2021)
Unsustainable and illegal wildlife trade is a well-known conservation issue, but there are still large gaps in understanding of how trade chains operate for the majority of over-exploited wildlife products. In particular, the large-scale global plant trade is under-reported and under-researched, which is even more pronounced when the trade takes place within a country’s borders. A clear example is the trade in orchids, all species of which are listed by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Although countries such as Vietnam are known hotspots for the large-scale collection of wild orchids for the international trade, little is known about how plants move from the wild to the end-consumer, the role played by domestic markets and the sustainability of trade. We use a mixed-methods approach to determine the structure of trade chains for orchids in key trading areas of Northern Vietnam, and use a thematic framework to identify five groups of actors trading wild-harvested orchids. Trade occurs both domestically and internationally, underpinned by demand for rare, wild plants. An important first step to address the illegal and unsustainable plant trade is to recognise it as a major conservation issue, and develop diverse approaches that consider the complexity of the supply chains involved. It is imperative that the scale and process of domestic trade is understood, and its impact on long term conservation of these species assessed to make more informed decisions about effective interventions that take into account the full supply chain.